KIDUNG RUMEKSA ING WENGI (Studi Tentang Naskah Klasik Bemuansa Islam) - Achmad Sidiq (Analisa: Journal of Social Science and Religion, 2008)
Kidung Rumeksa ing Wengi (precaution at night) is a songcomposed by Sunan Kalijaga. He is one of Walisongo, Islamicmissioner in Java. He is well known because of his skills and wisdomin propagating Islam with its source in Al 'Quran and Al-Hadist bytransforming it into Javanese community through various missionarymedium. One of them is his teaching in Javanese prayers (charms).Prayers in Javanese are often in form of songs or charmssince it is believed has magical power for those who practice it. Kidung Rumeksa ing Wengi, this charm is also known as "MantraWedha ". So it called because it could attract magical powers toprotect and cure (Chodjim, 2003: 15).Kidung Rumeksa ing Wengi contains theologicalphilosophic message in Dandhang Gula form that consists of nine verses along with performing asceticism and its pragmatic functionspecifically could protect the doer, especially at night. The first jiveverses must be performed at night and the rest four show how toperformance them. Spelling this charm will be protected from theevil spirit, devil, and black magic such as: fortune telling and otherbad-intention people, and could be cured from all diseases.